Aadhunik Europe ka itihas - Paruthi R.K., Bhandari Deepa (Arjun publishing house, Nai Delhi, 2009)
History
UGC XIth Five Year Plan 2009-2010
HINDI
Keywords: Aadhunik Europe ka itihas; History; History